Structure of DyFe2/YFe2 Laves phase superlattices grown by molecular beam epitaxy - Bentall, M; Ward, R; Grier, E; Wells, MR (2003)
The crystal structure of a series of six high quality single crystal Laves phase superlattice samples, of structure [t1 ÅDyFe2/t2ÅYFe2]N, grown by molecular beam epitaxy have been probed using a high resolution triple crystal x-ray diffractometer. A study of the scattering near the 2 2 0, 4 4 0 and 2 6 2 reflections has revealed the presence of several superlattice peaks, showing that the samples exhibit a high degree of superlattice modulation. The typical mosaic spread is less than 0.9°, while the superlattice coherence lengths are typically 2000 Å. Fitting of a model to the data using a differential evolution algorithm with a Rietveld refinement has confirmed the high quality of these samples and shows that the interface widths are typically ∼20 Å. Measurements of the in-plane and out-of-plane lattice parameters show that the samples are subjected to a shear that is slightly anisotropic in the plane. Transverse scans through the Bragg and superlattice peaks show that the width is mainly dominated by a mosaic crystal effect, with a small contribution arising from the correlated roughness at the bilayer interfaces. Finally, high resolution electron microscopy images show directly that these superlattices exhibit a high degree of modulation.